MicroRNA targeting microtubule cross-linked protein (MACF1) would suppress the invasion and metastasis of malignant tumor. (July 2017) - Zhao, Wenpeng; Qian, Huiming; Zhang, Ruisan; Gao, Xingchun; Gou, Xingchun
Abstract: Cancer is one of the most serious diseases that endanger human health in the world today, and the incidence and mortality of cancer increases year by year. Invasion and metastasis is the most prominent feature of malignant tumors, but also becomes the primary factor of threatening patient's health. Tumor cell invasion and metastasis which closely related to the dynamic changes of the cytoskeleton is an important factor influencing the survival of patients. Therefore, inhibition of tumor cell invasion and metastasis is a key strategy for the treatment of cancer. MACF1 is a microtubule microfilament cross-linking factor that plays an important role in cell polarization, cell migration, and maintenance of tissue integrity. A lot of studies have shown that microRNAs play an important role in tumorigenesis, invasion and metastasis. Therefore, we propose the following scientific assumptions: MACF1, an important molecule in adjusting the invasion and metastasis of tumor cells, regulates microfilaments, microtubules participating in cytoskeleton dynamics to promote malignant tumor cell migration and invasion; MicroRNA targeting MACF1 can decrease the expression of MACF1 and thus disrupt the dynamic balance of microtubule or microfilaments as an effective way to inhibit the invasion and metastasis of tumor cells. So we can use it as a new target for clinical early diagnosis and treatment of malignant tumor invasion and metastasis.